1996
DOI: 10.1006/gcen.1996.0010
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Detection of Parathyroid Hormone-Related Protein in the Saccus Vasculosus of a Teleost Fish

Abstract: Using antisera to regions of human parathyroid hormone-related protein (PTHrP) the saccus vasculosus (SV) of the sea bream (Sparus aurata) has been shown to contain immunoreactive PTHrP. By immunohistochemistry (IHC) the epithelial coronet cells in fixed and waxembedded SV tissue reacted with antisera to the prepro region of human PTHrP (−13 to +2), the N-terminus PTHrP (1-16), and the midmolecule PTHrP (50-69). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of saccus extracts and incubation media c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…However, many organs such as the brain, the choroid, the saccus vasculosus (a peculiar organ for detecting water pressure), the pituitary gland, the kidney and the rectal gland showed the immunoreactivity (Ingleton et al, 1993). However, using immunohistochemistry and electron microscope, Devlin et al (1996) obtained results that led them to reaffirm that in the sea bream, only the saccus vasculosus produces PTHrP,.…”
Section: The Origin Of Pthrp Is Oldmentioning
confidence: 98%
“…However, many organs such as the brain, the choroid, the saccus vasculosus (a peculiar organ for detecting water pressure), the pituitary gland, the kidney and the rectal gland showed the immunoreactivity (Ingleton et al, 1993). However, using immunohistochemistry and electron microscope, Devlin et al (1996) obtained results that led them to reaffirm that in the sea bream, only the saccus vasculosus produces PTHrP,.…”
Section: The Origin Of Pthrp Is Oldmentioning
confidence: 98%
“…PTHrP was quantified in plasma by radioimmunoassay using heterologous antisera raised against human peptide (Danks et al, 1993;Devlin et al, 1996) and later with homologous antisera (Rotllant et al, 2003;Abbink et al, 2004Abbink et al, , 2006. As holds for elasmobranch species, PTHrP levels in teleostean plasma are consistently and significantly higher than these values for humans (basal circulating lev els of around 0.5-2.5 pmol l_1 in humans and 0.1 0.6 nmol l_1 in fish).…”
Section: Pthrp In Teleostsmentioning
confidence: 99%
“…In-situ hybridisation (Danks et al, 1998;Trivett et al, 1999;Ingleton et al, 2002) and immunohistochemical stud ies (Devlin et al, 1996;Trivett et al, 1999;Flanagan et al, 2000) have demonstrated the pthrp mRNA and PTHrP protein in gills, operculum, kidney, pituitary gland, brain, saccus vasculosus, muscle, skin, spleen, liver and intestine. This widespread distribution of the pthrp gene and protein reflects the wide range of functions that are reported for PTHrP in fish and suggests endocrine, paracrine, autocrine and intracrine functions; at this moment, no reports on intracrine effects in fish tissues are available.…”
Section: Pthrp In Teleostsmentioning
confidence: 99%
“…Although recent reports indicate that fish express PTH (Danks et al, 2003;Gensure et al, 2004), they also have PTHrP, which has a number of physiological functions, such as bone development, placental calcium transport and cellular growth and development (Martin et al, 1997). In sea bream (Sparus auratus L.), PTHrP has been detected in several tissues and plasma by radioimmunoassay using antisera raised against the human peptide (Danks et al, 1993;Devlin et al, 1996) and, more recently, the sea bream peptide (Rotllant et al, 2003). PTHrP has also been found in several other fish species Danks et al, 1998;Trivett et al, 1999Trivett et al, , 2001).…”
mentioning
confidence: 99%